The jungle books - Kipling, Rudyard, 1865-1936. (Southport, CT : Levin, Hugh Lauter Assocs., 1992)
Presents the adventures of Mowgli, a boy reared by a pack of wolves and the wild animals of the jungle. Also includes other short stories set in India.
Includes bibliographical references.
Keywords: Animals -- Fiction; Mowgli (Fictitious character) -- Fiction; Jungles -- Fiction; Short stories; India -- Fiction